Aspects of negation in Otjiherero (Journal for Studies in Humanities and Social Sciences, 2016)
The purpose of this article is to provide a detailed description of Otjiherero negative grammatical features; to show how negation behaves in Otjiherero expressions; the effect of negation on meanin; the concomitant phonological processes involved; and to determine whether negation reveals Otjiherero sentence structures in general. As Möhlig and Kavari (2008, p.166) put it; “…in independent tenses, negation is expressed by the prefi x hi- for 1st person singular and by ka- for all other persons and classes”, while ha negates all subordinate clauses. Double negation in Otjiherero is a matter of emphasis, although in the Kaoko dialect it is used in a normal way in certain contexts, and though it is not used at all in the central dialect of Otjiherero. As Dembetembe (1986, p. 1) states: “…linguistically affi rmation or negation is a feature of the predicate, the nucleus of which is the verb, whether this is expressed overtly or latently in surface structure”, investigating how negation of predicates works seems to be an appropriate descriptive approach.